Penggunaan Abu Ampas Tebu (Bagasse Ash Of Sugar Cane) sebagai Bahan Pengganti Filler pada Campuran Aspal Panas (Hot Mix) Latasir B - Alik Ansyori Alamsyah; Hari Eko Meiyanto (Media Teknik Sipil, 2016)
From year to year the Portland cement ( PC ) are known to have the price up and down. The Portland cement ( PC ) is used as a filler for asphalt mix is very limited , so it sought an alternative to the use of filler . The existence of abundant ash bagasse in sugar mills Indonesia is still not utilized properly . For now bagasse ash in Indonesian factories only used as fertilizer for sugarcane . This study aims to investigate the performance of hot mix asphalt ( HOT MIX ) LATASIR type - B ( HRSS - B ) with bagasse ash as filler material substitution using a variation of the collision. Specimens are made comprised of three major groups , namely : the test specimen using cement and bitumen of penetration 80/100 ( PC ) , the test object using bagasse ash and bitumen of penetration 80/100 with ( U.S. ) and the test object using the ash residue cane with a variation of the collision and penetration bitumen 80/100 with ( U.S. ) . Total specimen made amounted to 45 , for each type of mixture made 15 test specimens . For ( PC ) Levels of asphalt used is at 6.90% , 7.90% , 8.90 % , 9.90 % , and 10.90 % . Specifications are used to follow the standard Ministry of Settlements and Regional Infrastructure in 2001 using the Marshall method. Filler levels for each of the mixtures was 8.13% and 7.40% OBC generated . For ( AT ) levels fiiler used is 5.00 % , 10.00 % , 15.00 % , 20.00 % , and 25.00 % OBC for each - each mixture was 7.40% and the resulting levels of filler optimum bagasse ash of 7.10 % . Characteristic strength of the mixture based on the value of the stability conditions of the OBC and optimum filler levels . Carrying capacity of filler cement ( PC ) in a mixture of filler OBC 7.40% 8.13% yield and stability of the value of 720 kg , the carrying capacity of bagasse ash ( AT ) in a mixture of 7.40% OBC and filler 7.10% yield stability values 823.35 kg , while carrying a mixed impact on OBC 45 7.40% 7.10 % filler and produce value stability 840.66 kg.